The Matching Status Between Donor and Recipient Hepatitis B Seroepidemiology Makes a Difference in Liver Transplantation for Hepatocellular Carcinoma. Issue 5 (1st May 2020) - Lu, Di; Yang, Fan; Zhuo, Jianyong; Yang, Modan; Lin, Zuyuan; Jin, Pingbo; Cai, Xuechun; Cen, Beini; Wang, Jianguo; Wei, Xuyong; Zheng, Shusen; Xu, Xiao
Abstract : INTRODUCTION: Antibody to hepatitis B core antigen (HBcAb) is known to be related with the prognosis for patients with hepatocellular carcinoma (HCC). This study aims to evaluate the prognostic capacity of HbcAb and other donor/recipient hepatitis B seroepidemiological indexes in transplantation for HCC. METHODS: Based on the national liver transplant registry, we analyzed the prognostic capacity of HBcAb in liver transplantation for patients with HCC of different etiological backgrounds. The hepatitis B virus (HBV)-related HCC cohort was further studied regarding donor/recipient hepatitis B seroepidemiology, and then divided into a training cohort (n = 1, 222) and a validation cohort (n = 611) to develop a pretransplant recurrence-risk predicting nomogram. RESULTS: Positive HbcAb in recipients was related to an increased risk of post-transplant tumor recurrence in HBV-related (n = 1, 833, P = 0.007), HCV-related (n = 79, P = 0.037), and non-B non-C HCC (n = 313, P = 0.017). In HBV-related HCC (n = 1, 833), donor hepatitis B surface antigen (HbsAg) was also associated with post-transplant tumor recurrence ( P = 0.020). Multivariate analysis showed that the matching status of recipient HbcAb and donor HbsAg (MSHB) was an independent prognostic factor ( P = 0.017). HbcAb-positive recipients matched with HbsAg-positive donors displayed the worst post-transplant outcomes ( P < 0.001). In the training cohort (n = 1, 222), a risk-predicting nomogram was established based on α-fetoprotein, Milan criteria, and MSHB. The model showed excellent prognostic capacity and safely expanded Milan criteria in both training and validation cohorts ( P < 0.001). DISCUSSION: Positive HbcAb in recipients increases the risk of post-transplant tumor recurrence in HCC with different etiological backgrounds. The nomogram based on MSHB is effective in predicting tumor recurrence after transplantation for HBV-related HCC.